Quantifying insects richness under Riparian and Rehabilitation Forest canopies, Sarawak, Malaysia - Abu Bakar, Nurul Asyiqin; Mohamad, Azlin Farahin; Abdul Halim, Amir Akmal; James Gerusu, Geoffery; Empin, George Bala (2019)
Insects are the largest and more diverse group of organisms on Earth that can be found everywhere especially in the forests. Over the decades, as far as we know, until today there have been limited research were conducted an experiment on insects between Riparian and Rehabilitation Forest. The Riparian forest with coordinate 3 ° 12'33.6 "N 113 ° 05'40.4" E and Rehabilitation Forest with coordinate 03“12’16.7” N 113 “04’04.9” E which located at Bintulu, Sarawak, Malaysia. The study objectives were:identifying the insects order in two different canopies identifying and computing insect biodiversity index richness determine the efficiency of insect trapping. There are four sampling methods employed as 16 pitfalls, 1 light trap, 1 yellow-pan trap, and sweep net. The sampling duration were employed eight weeks at each location. Based on our findings on this research, the most efficient method is by using the sweep net because sweep net is the easiest way to catch the insects because it allows us to move around to catch the insects especially the flying one.